(untitled) (Social Science Review, 2022)
The Tanguar Haor is overwhelmed with huge problems such as flash floods, poverty, extreme dependency on natural resources, lack of alternative sources of income, inadequate health facilities and sanitary latrines, scarcity of potable water, poor road connectivity, the insufficient and flimsy infrastructure of educational institutions. The main objective of this research is to find out the core causes of these problems and to examine how these problems make hindrances to ensure equal access to primary education in Tanguar Haor. Simultaneously, this study has analysed the existing scenario of primary education in this area. Both qualitative and quantitative approaches have been incorporated in this fieldwork-based study. The survey, FGD, and KII methods have been applied in this research to collect primary data from sixty (60) respondents of purposively selected villages and primary schools. The researcher has identified major drawbacks such as poverty, dropout, high repetition, absenteeism in school, shortage of enough teachers that create serious obstacles towards ensuring equal access to primary education in the Tanguar Haor of Sunamganj District. Finally, this study concludes that climate change-induced threats and environmental vulnerabilities are mainly responsible for producing these snags. Social Science Review, Vol. 38(1), June 2021 Page 175-202